2016
DOI: 10.1038/srep31995
|View full text |Cite
|
Sign up to set email alerts
|

UPF1 regulates myeloid cell functions and S100A9 expression by the hnRNP E2/miRNA-328 balance

Abstract: UPF1 is a key player in nonsense mediated mRNA decay (NMD) but also involved in posttranscriptional gene regulation. In this study we found that UPF1 regulates the expression of genes with functions in inflammation and myeloid cell differentiation via hnRNP E2. The majority of the UPF1-regulated genes identified in monocytic cells contain a binding site for hnRNP E2 within 5′ UTR located introns with hnRNP E2 acting here as splicing regulator. We found that miRNA-328 which is significantly induced during monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…For example, UPF1 regulates tumorigenesis by targeting Smad7 in hepatocellular carcinoma [21]. And UPF1 regulates myeloid cell functions and S100A9 expression by the hnRNP E2/miRNA-328 balance [35]. In this study, we found that UPF1 was also downregulated in gastric cancer.…”
Section: Discussionsupporting
confidence: 52%
“…For example, UPF1 regulates tumorigenesis by targeting Smad7 in hepatocellular carcinoma [21]. And UPF1 regulates myeloid cell functions and S100A9 expression by the hnRNP E2/miRNA-328 balance [35]. In this study, we found that UPF1 was also downregulated in gastric cancer.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies proved that UPF.1 knockdown caused hnRNP-E2 overexpression. Hence, it will decrease the expression SI00A9 which also an important regulator for myeloid differentiation [30].…”
Section: Discussionmentioning
confidence: 99%
“…TRIB-2 could also induce the degradation of CEBPA protein. On the other hands, CEBPA protein interaction with AML1-ETO or c-jun was also known to inhibit the function of CEBPA itself [29][30][31][32][33]. It assumed that there are many factors that regulate the CEBPA expression and its activities in myeloid differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…This function is independent of the miR's seed region and operates exclusively by interference with a RBP. It was shown for the first time for miR-328 which acts as RNA decoy for the heterogeneous nuclear ribonucleoprotein E2 (hnRNP E2), a global gene expression repressor (Eiring et al, 2010;Saul et al, 2016Saul et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%